DWT-SVD Combination Method for Copyrights Protection - Kusumaningrum, Desi Purwanti; Rachmawanto, Eko Hari; Atika Sari, Christy; Pradana, Rizky Putra (Scientific Journal of Informatics, 2020)
Many irresponsible people who download other people's artwork then modify and redistribute the work of someone without permission by not including the owner's name. Based on that problem an attempt was made to provide an invisible watermark so as not to be easy to do the watermark removal process on the artwork, using a 2-level DWT and SVD combination method that can embed watermarks invisibly and increase watermarking resistance to the image from various image manipulation processes such as noise, JPEG compression, and so on. From combination method of DWT-SVD got the highest PSNR value with watermark image size 32x32 and 64x64 which is 59.2656 dB and 54.7414 dB, respectively.